KEBEBASAN BERAGAMA DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA - Merlien Irene Matitaputty (Faculty of Law, Universitas Pattimura, 2015)
Human rights are essentially a reflection of human existence, because human rights was the formation of human wholeness that leads to civilized life. On the basis of this that the violation of ham is the most dangerous crime civilization. Belief in human rights is essentially a form of human sympathy and empathy for him and others. HAM then experienced a shift from a form of consciousness imaginary then incarnated in the form of measurable and concrete. Various problems that occur in the community showed the need for a government action that comes from the rule of law as an instrument providing legal protection for the people. But sometimes concrete actions the government relating to the legal protection to the people in the form of decisions - decisions and decrees of the government often unilateral and it is very noticeable when the government, through the Minister of Religious Affairs, Ministry of Interior and the Attorney General issued a Joint Decree concerning the Prohibition Activity Ahmadia in Indonesia, which resulted in the violation of human rights, especially the right to worship. Along with the expansion of life, we need fundamental regulations that are considered capable of bridging the diverse interests that occasionally explode due to pressure individual and communal. Thus, the Constitution is a manifestation of a form of a shared desire that gives the rules towards a civilized nation.